Studi Empiris Mengenai Penilaian Kinerja Jurusan di Bidang Penelitian Menggunakan Data Enevelopment Analysis (DEA) - Farikhin, Farikhin; Noranita, Beta (JSINBIS (Jurnal Sistem Informasi Bisnis), 2013)
Performance evaluation of academic departments in university become routine activity to improve quality service.There qualitative and quantitative aspects to evaluate academic department. As well known that Data Envelopment Analysis (DEA) is one of non parametric technique based on linear programming. In this paper, we study to evaluate the academic departments with data envelopment analysis based on quantitative aspects. We formulate the performance evaluation as DEA problem. There are several stage to build DEA model as tool for the performance evaluation of academic departments. Firstly, we investigate purely quantitative variables in departement as input/output DEA model. Secondly, we discuss several ranking methods of decision making unit (DMU) to obtain efficiency of academic departments. In this paper, we use modified l1-norm method to rank DMU’s in DEA model. Keywords : DEA, DMU, and modified l1-norm method